Free acquisition of psychotropic drugs by the Brazilian adult population and presence on the National List of Essential Medicines - Patrícia Silveira Rodrigues; Priscila Maria Stolses Bergamo Francisco; Andréia Turmina Fontanella; Karen Sarmento Costa (Universidade de São Paulo, 2022)
Abstract The aims of the present study were to estimate the free-of-charge acquisition of psychotropic drugs among Brazilian adults; analyze the distribution of psychotropics according to their presence on the Relação Nacional de Medicamentos Essenciais (RENAME [National List of Essential Medicines]) and acquisition according to the source of funding (free of charge or direct payment); and estimate the proportion of free-of-charge psychotropic drugs according to therapeutic class and presence on the RENAME. This study involved the analysis of data from the 2014 National Survey on the Accessibility, Use and Promotion of the Rational Use of Medicines considering psychotropic drugs used by the adult population (≥20 years; n = 32,348). The prevalence of the acquisition of free-of-charge psychotropic drugs was 53.3% and 64.6% of these drugs were on the RENAME. Among the psychotropic drugs acquired by direct payment, 70.8% were not on the national list. Regarding free-of-charge acquisition according to the therapeutic class and presence on the RENAME, differences were found for antidepressants, anxiolytics and antipsychotics (p <0.05). In conclusion, the most used psychotropic medicines were listed in the RENAME, but free-of-charge acquisition was not provided for all of them.